Jack Bean Urease Inhibitors, and Antioxidant Activity Based on Palmitic acid Derived 1-acyl-3- Arylthioureas: Synthesis, Kinetic Mechanism and Molecular Docking Studies - Saeed, Aamer; ur-Rehman, Sajid; Channar, Pervaiz Ali; Larik, Fayaz Ali; Abbas, Qamar; Hassan, Mubashir; Raza, Hussain; Seo, Sung-Yum (Drug Research, 2017)
A series of acylthioureas was synthesized and their inhibitory effects on the DPPH and jack bean urease were evaluated. The results showed that all of the synthesized compounds exhibited significant jack bean urease inhibitory activities. Especially, 1-(4-chlorophenyl)-3 palmitoylthiourea 5a bearing 4-chloro substituted phenyl ring exhibited the most potent tyrosinase inhibitory activity with an IC50 value 0.0170 μM compared to the IC50 value of 4.720 μM of thiourea used as standard. The inhibition mechanism analyzed by Lineweaver–Burk plots revealed that the type of inhibition of compound 5a on tyrosinase was noncompetitive. The docking study against jack bean urease enzyme was also performed to determine the binding affinity of the compounds. The compounds 4c and 4e showed the highest binding affinity with the active binding site of tyrosinase. The initial structure activity relationships (SARs) analysis suggested that further development of such compounds might be of interest. The statistics of our results endorses that all compounds and particularly 5a may serve as a structural template for the design and development of novel urease inhibitors Graphical Abstract.
Keywords: antioxidant; Jack bean Urease; synthesis; acylthioureas; molecular docking; kinetic mechanism